Gambaran Perilaku Penghuni Indekos di Sekitar Kampus Universitas Tanjungpura dalam Membuang Sampah - Meifira, Athalia; Akbar, Aji Ali; Saziati, Ochih (Jurnal Teknologi Lingkungan Lahan Basah, 2023)
One factor that has an influence on the comfort of the residence is the cleanliness of the residence. The habit of disposing of garbage is closely related to the cleanliness and comfort of the residence. Dormitory residents have an important role in maintaining the cleanliness of the dormitory. When boarders dispose of garbage in its place, it has a positive effect on the cleanliness of the dormitory environment. So this study was conducted to determine the behavior of dormitory residents in disposing of garbage and the condition of the availability of public dormitory bins. Data samples taken in this study were using purposive sampling method with the research location, namely dormitory around Universitas Tanjungpura with a radius of 1 kilometer from Universitas Tanjungpura. Data collection in this study by direct survey to respondents using a questionnaire. The results showed that 76.25% of dormitory around Universitas Tanjungpura already have public trash facilities for each occupant. The behavior of residents in disposing of garbage still needs to be improved because 60.00% of dormitory residents still do garbage disposal every few days. Then for the location of garbage disposal is classified as good, 98.75% have disposed of garbage in the trash cans.